Programming Logic Learning: a student model for collaboration groups - Diemer, Mouriac (2023)
This work presents the definition and validation of a Supportive Collaborative Student Model, aiming to aid the formation of collaborative groups for learning programming logic. The model was developed from studies on affectivity, based on Scherer, and collaborative learning. Techniques from Affective Computing were used. Subsequently, the groups with students conforming to the model were compared to the other groups in order to analyze the influence of supportiveness on the learning of programming logic. The study revealed performance differences that may be associated with the presence of supportive interpersonal stance students.